Transformative pathways: understanding economic growth in Africa using the African Transformation Index - Eugene Msizi Buthelezi (Cogent Economics & Finance)
This study investigates the critical role of structural transformation in African economies and its significance for inclusive growth, utilizing the African Transformation Index (ATI). The core focus is to understand how structural transformation influences economic growth and to highlight key factors driving this process. By employing a Cobb-Douglas production function and panel quantile regression analysis on data from 30 African countries from 2000 to 2022, the research aims to fill a gap in the literature on African economic development. The major findings reveal that the ATI positively impacts GDP per capita growth rates, especially at lower quantiles, indicating that structural transformation is vital for inclusive growth. Conversely, diversification negatively affects growth, highlighting the challenges of overly diversified economies. Additionally, export competitiveness and productivity improvements contribute positively to growth, while technology upgrading shows significant impact mainly at lower quantiles. Human well-being is identified as a crucial driver of growth, particularly at middle quantiles. The significance of these findings lies in their policy implications: prioritizing structural transformation, enhancing export competitiveness, improving productivity, and focusing on human well-being are essential for achieving sustainable and inclusive growth in Africa. This research provides empirical evidence on the importance of structural transformation and offers valuable insights for policymakers aiming to foster sustainable development in African economies.